Newsprint Grade Refiner Ground Wood Pulp from Jute Sticks (Corchorus capsularis) - Mukherjea, V. N.; Sharma, Y .k.; Guha, S. R. D. (Indian Forester, 1971)
Laboratory experiments on the production of mechanical pulp from jute sticks by refiner groundwood process are described. Standard pulp-sheets were made from a mixture of 60 per cent mechanical pulp from jute sticks and 40 per cent bleached sulphate pulp. The strength properties and brightness of the standard-sheets made under suitable conditions have shown that jute sticks are an ideal raw material for the production of newsprint.